PENGARUH LEADER MEMBER EXCHANGE TERHADAP KINERJA DOSEN UNIVERSITAS MUHAMMADIYAH CIREBON - JAENUDIN JAENUDIN (Institut Bisnis Muhammadiyah Bekasi, 2021)
Knowledge management in the world of Education is increasingly important as a research topic, especially in the effort to improve the performance of lecturers in a university. Human resources are assets that must be safeguarded, the role of lecturers as HR is very important in improving the quality or quality of a college, especially at the University of Muhammadiyah in Cirebon. This research aims to describe leader member of exchange and job performance. In addition, to find out whether there is a relationship between each variable both the relationship directly and indirectly. The approach used in this study is quantitative with a survey research design that uses the path analysis approach. The population of this study were all lecturers of the University of Muhammadiyah Cirebon (UMC) with a sample of 117 lecturers. The data collection technique uses an instrument in the form of a questionnaire. The results showed that the job performance of Muhammadiyah Cirebon University lecturers was influenced more dominantly by the Leader member of exchange variable. Based on the data found in the field it can be concluded that the performance of Muhammadiyah Cirebon University lecturers will be more prudent when lecturers are led by leaders who want to go directly involved with their subordinates in carrying out their work or leader member exchange (LMX). This is a finding that should be followed up in the hope of improving the performance of lecturers at the Muhammadiyah University in Cirebon